Contents and Foreword of the SOSIOHUMANIKA Journal, Issue of November 2016 - SOSIOHUMANIKA, Editor Journal (SOSIOHUMANIKA, 2016)
SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan. This journal, with print ISSN 1979-0112, was firstly published on May 20, 2008 in the context to commemorate One Millenium of National Awakening Day in Indonesian. The SOSIOHUMANIKA journal is published twice a year i.e. every May and November. For period 2013 to 2018, the SOSIOHUMANIKA journal has been accredited by Ditjendikti Kemdikbud RI (Directorate-General of Higher Education, Ministry of Education and Culture of the Republic of Indonesia). Since issue of May 2016 to date, the SOSIOHUMANIKA journal has been organized by the Lecturers of UPI (Indonesia University of Education) in Bandung; and published by Minda Masagi Press as a publishing house owned by ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia.Â Bandung, Indonesia: November 30, 2016.Prof. Haji Furqon, Ph.D.Honorable Patron of the SOSIOHUMANIKA Journal; and Rector of UPI in Bandung, West Java, Indonesia.Â